Forgone healthcare for medically vulnerable groups during the pandemic era: experiences of family caregivers of young adults with substance use disorders in Zambia - Kabembo, Ireen Manase (Frontiers in Public Health, 2024)
Introduction Scholars worldwide have defined the COVID-19 pandemic as a mass-disabling event of our time. The situation is grave for families experiencing financial hurdles while caring for young adults in recovery from addiction problems. Methods Using semi-structured interviews with 30 purposively selected family caregivers (FCGs) of young adults with substance use disorders (SUDs) in Lusaka, Zambia, this study reveals several factors influencing forgone healthcare for this medically vulnerable group. Results Financial challenges and huge out-of-pocket bills; caregivers’ perceived far-fetched recovery of the young adult; the cost of medication and transportation; the young adult’s little perceived need for healthcare service use, their runaway and treatment elusive tendencies; caregiver concerns about contracting the virus, and the stigma associated with it; and a fragmented child and adolescent mental health system influenced forgone healthcare. The young adults were often unavailable for days and months, posing challenges to the continuity of care. Despite caregivers’ acknowledgment of the availability of healthcare professionals, young adults with problematic substance use had limited access to SUD recovery services, resulting in adverse health outcomes. Results also show that most family caregivers encountered challenges in accessing and purchasing psychotropic medications, which were difficult to find during the lockdowns. Some family caregivers lost their sources of income by being laid off from work due to the pandemic and skipping work to attend to caregiving responsibilities. Most of those in self-employment had to close their business and stay home to look after their youth. Several caregivers kept their youth at home because they failed to access private residential SUD recovery services. Family caregivers mostly relied on outpatient public health services, alternative medicine from traditional healers, and faith-based healing, all of which some young adults rarely accessed because of their problematic behaviors of escaping healthcare. Conclusion These identifiable risk factors, and their detrimental consequences highlight the need for interventions to improve healthcare access for this vulnerable population. Supporting FCGs of addicted young adults is crucial in ensuring the well-being of both the caregivers and care recipients. Further research is warranted to explore potential solutions, such as peer support programs, policy changes, and education initiatives for carers and recipients in the (post) pandemic era.